2016
DOI: 10.1371/journal.pone.0163880
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of the Transmission Dynamics of Clostridium difficile Infection and Colonization in Healthcare Settings: A Systematic Review

Abstract: BackgroundWe conducted a systematic review of mathematical models of transmission dynamic of Clostridium difficile infection (CDI) in healthcare settings, to provide an overview of existing models and their assessment of different CDI control strategies.MethodsWe searched MEDLINE, EMBASE and Web of Science up to February 3, 2016 for transmission-dynamic models of Clostridium difficile in healthcare settings. The models were compared based on their natural history representation of Clostridium difficile, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Similarly, our model ranked restriction of high-risk antibiotics as more effective compared with reduction on the overall antibiotic use. Overall, antibiotic stewardship has been rarely evaluated in mathematical models for C. difficile; when evaluated, antibiotic stewardship was found to have low effectiveness in decreasing CDI [44]. Yacob et al [45] reported that antibiotic stewardship was ineffective in reducing clinical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our model ranked restriction of high-risk antibiotics as more effective compared with reduction on the overall antibiotic use. Overall, antibiotic stewardship has been rarely evaluated in mathematical models for C. difficile; when evaluated, antibiotic stewardship was found to have low effectiveness in decreasing CDI [44]. Yacob et al [45] reported that antibiotic stewardship was ineffective in reducing clinical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Becker et al did not find significant differences in the titer of viruses detected from three 25 cm 2 uncontaminated surfaces after wiping them with a QAC disinfectant wipe previously used on a contaminated surface [26]. The reported risk of cross-contamination by C. difficile spores is particularly relevant in healthcare settings as C. difficile infections have been associated with contaminated environmental surfaces [30,31,32].…”
Section: Disinfectant Wipes Cross-contaminate Hard Non-porous Surfacesmentioning
confidence: 92%
“…We implemented the model stochastically, and used the Gillespie direct algorithm to simulate the stochastic model within a (non-ICU) hospital ward with 50 beds (as the population size) within the range of previous studies for C. difficile [18]. To estimate the transition time between the two consecutive events in the stochastic process, we let dt  =  − log( n 1 )/ Δ , where n 1 is a random number drawn from the uniform distribution on the unit interval [0 , 1], and Δ is equal to the sum of the rates for all possible events.…”
Section: Methodsmentioning
confidence: 99%